MENINGKATKAN HASIL BELAJAR IPA MELALUI PEMBELAJARAN COOPERATIVE LEARNING TIPE MAKE A MATCH DI MADRASAH IBTIDAIYAH - Hasni, Nurie; Lisnawati, Santi (Program Studi PGMI, 2019)
This study aims to describe the steps of using cooperative learning learning method type make a match in improving science learning outcomes of grade IV students MI Mathla'ul Anwar. This study uses classroom action research methods carried out in 3 cycles. In the cycle consists of planning, action, observation and reflection. The subject of the study was the fourth grade student of MI Mathla'ul Anwar Caringin in the 2018/2019 school year. The method of analysis in this study uses descriptive statistics. The instrument used is a formative test given after learning is complete. The results showed that in the first cycle there were 6 students who were completed and 20 students who had not yet completed, with an average of 60.38%, then in cycle II there were 18 students who were complete and 9 students who had not completed with an average score of 71.15% , then in the third cycle students who achieved complete were 26 students or the fourth grade students with an average score of 81.69%. Teacher activity in the first cycle obtained a percentage of 71.73%, in the second cycle obtained a percentage of 79.34%, and in the third cycle obtained a percentage of 85.86% with a very good category. Student activities in the first cycle obtained a percentage of 66.66%, in the second cycle obtained 72.22%, and in the third cycle obtained 91.66% in the very good category. Based on the results of the above research, it can be concluded that the method of cooperative learning learning type of make a match can improve the learning outcomes of grade IV science at MI Mathla’ul Anwar Caringin, Bogor.